The use of health data to foster the development of clinical trials through value-based healthcare in Portugal (Journal of Statistics on Health Decision, 2021)
The value-based healthcare (VBH) approach has emerged as an alternative to the traditional management of health systems. However, it is still necessary to evaluate its impacts in several domains, including the management of clinical trials.This study aims to analyse how the healthcare ecosystem in Portugal is implementing VBH and how that can enhance the management and implementation of clinical trials. For that, interviews were made with elements involved in the implementation of VBH in Portugal, that were complemented with secondary data analysis in order to obtain a preliminary perspective on the subject.The sources emphasized that, even though it VBH is considered an important development in health management, in Portugal it is still difficult to efficiently collect data from the different elements, especially patient measurements, and that patients still fear the non-clinical use of the data provided.With this background, in order to fulfill the potential of data to foster clinical trials, there is the need to develop new ways of collecting and managing data from the stakeholders, and there is also the need to have innovative approaches to information sharing to foster innovation and patient participation.These findings support the broader concept that there is an underlying opportunity to develop integrated information systems where data from patients can be collected, (pseudo) anonymized and used to foster innovation, while, at the same time, creating a symbiosis between the implementation of VBH concepts and the development of clinical trials.This work can serve as basis for future research regarding the use of data in the health system, aligned with broader initiatives such as the creation of the Portuguese Health Data Lake and the European Health Data Space, aligned with a dynamic clinical trials industry.